Are the Follicular Fluid Characteristics of Recovered Coronavirus Disease 2019 Patients Different From Those of Vaccinated Women Approaching in vitro Fertilization? - Castiglione Morelli, Maria A.; Iuliano, Assunta; Schettini, Sergio C. A.; Ferri, Angela; Colucci, Paola; Viggiani, Licia; Matera, Ilenia; Ostuni, Angela (Frontiers in Physiology, 2022)
The aim of this pilot study is to evaluate if SARS-CoV-2 infection or vaccination against SARS-CoV-2 infection induce observable metabolic effects in follicular fluid of women who are following in vitro fertilization (IVF) treatments. The possible impact of COVID-19 on fertility and IVF outcome is considered. We have selected for this study: 6 women vaccinated against SARS-CoV-2 infection, 5 recovered COVID-19 patients, and we used 9 healthy women as the control group. At the time of oocytes retrieval from participants in the study, follicular fluids were collected and metabolomic analysis was performed by 1H NMR spectroscopy in combination with multivariate analysis to interpret the spectral data. The search for antibody positivity in the follicular fluid aspirates was also carried out, together with the western blotting analysis of some inflammatory proteins, interleukin-6, tumor necrosis factor  and the free radical scavenger superoxide dismutase 2.